Liberating the Publications of a Distinguished Scholar: A Pilot Project. - Julie Kelly (Issues in Science and Technology Librarianship)
Many distinguished scholars published the primary corpus of their work before the advent of online journals, which makes it more challenging to access. Upon being approached by a distinguished Emeritus Professor seeking advice about getting his work posted online, librarians at the University of Minnesota worked to gain copyright permissions to scan and upload older works to the University's Digital Conservancy (UDC). This project then uniquely took the process one step further, using the sharing option of RefWorks to make these works accessible to the widest possible audience while concurrently offering the sophisticated functionality of a citation manager. With open access repositories gaining acceptance as an authoritative long-term venue for making resources available online, including older content that can be digitized, the methods developed in this pilot project could easily be followed by others, thus greatly increasing access to older literature from distinguished scholars. [ABSTRACT FROM AUTHOR]